Stable interindividual differences in modafinil’s effect on vigilance during sleep deprivation - Van Cutsem, Jeroen; Van Puyvelde, Martine; Van den Berg, Nicholas H.; Dessy, Emilie; Detaille, Frederic; Van Rompay, An; Mairesse, Olivier; Drogou, Catherine; Sauvet, Fabien; Neyt, Xavier; Pattyn, Nathalie; Simonelli, Guido (Frontiers in Pharmacology, 2025)
RationaleIn specific operational contexts (i.e., military aviation), the off-label use of modafinil is officially regulated. However, safety concerns are still raised.ObjectivesTo study the stability and robustness of interindividual differences in modafinil sensitivity, both in terms of risks and benefits in military student pilots.MethodsEleven healthy military student pilots (21 ± 2 yr; 1 woman) were tested in a within-subject randomized counterbalanced crossover design to compare modafinil (2 × 200 mg; EXP) vs. placebo (CON) effects during extended wakefulness (24 h). Throughout both trials, participant’s vital signs, mood, vigilance [i.e., Psychomotor Vigilance Task (PVT)] and self-monitoring ability were measured. Additionally, four participants were genotyped [i.e., COMT (rs4680) and PER3 (rs228697)]. We used Pearson correlation coefficients to evaluate the relationship between PVT performance and the performance self-monitoring scores. To evaluate the stability of interindividual differences in the effectiveness of modafinil to improve PVT performance and sleepiness, an intraclass correlation coefficient (ICC) was calculated for the delta score (CON-EXP) of both outcome measures.ResultsModafinil significantly improved PVT performance (p ≤ 0.034) and sleepiness (p ≤ 0.029) at 2a.m. and 4a.m. during the sleep deprivation night. The stability of the non-adjusted reaction time-delta score was very high (ICC = 0.90). Non-adjusted reaction time only correlated with the performance self-monitoring scores in CON (r ≥ −0.35; p < 0.001).ConclusionStable interindividual differences in the effectiveness of modafinil to counteract the sleep deprivation-associated decrease in vigilance exist. Further research should focus on quantifying the extent to which modafinil-induced overconfidence and subjective rebound sleepiness actually constitute potential problems in operational environments (e.g., perhaps using war game simulations).